The Improvement Path of the Miao’s Abduction Marriage Customs from a Legal Perspective - Peidong Yu (Law and Economy, 2023)
Abduction marriage is a traditional custom among the Miao nationality, and its traditional forms mainly include abduction by local landlords, opposition to parental influence, and opposition to high dowry. After the founding of new China, with the promotion of women’s status and the awakening of the rule of law, the traditional abduction marriage customs of the Miao people have evolved into a new civilized form. In practice, there are still a few Miao men who engage in illegal activities of abduction marriage under the guise of traditional customs to avoid criminal punishment. Legislative bodies can make relevant laws and regulations to regulate such traditional customs. When determining such cases, judicial authorities should refer to relevant laws and regulations, and may inquire about local Miao nationality to understand local customs, comprehensively consider the harmfulness of the perpetrator’s behavior, and determine whether to hold them criminally responsible, in order to safeguard the legitimate rights of Miao women.